The implementation of e-learning with team builder at vocational high schools - Mahmud Al Haq Patwary; Herman Dwi Surjono (REID (Research and Evaluation in Education), 2015)
This research is aimed at: (1) producing an appropriate e-learning for English language studies in vocational high school, (2) evaluating the suitability of the developed e-learning in terms of appropriateness, accuracy and clarity, screen presentation and design, and appropriateness of the team builder module aspect, and (3) evaluating the effectiveness of the e-learning in practical application. This research and development (R&D) study used Alessi and Trollip’s model rearranged following ADDIE model, where the development of instruction followed Dick and Carey’s model and the need assessment procedures were adapted from Lee & Owens. Overall appropriateness and quality of the e-learning from alpha testing is ‘very appropriate’ and from beta testing is ‘excellent’. Alpha testing reveals that, the Team Builder Module is ‘very appropriate’ and beta testing reveals that, its overall quality is ‘excellent’. The e-learning is highly effective. The average score of the students raises 3.82 points (or 42.44%) in the post-test from pre-test score. The minimum score of the post-test (i.e. 8) is more than the maximum score of the pre-test (i.e. 7), so it is concluded that the use of e-learning does not deteriorate the performance of the students, but improves their performance.